PROSES PEMBENTUKAN KARAKTER RELIGIUS ANAK ASUH DI LEMBAGA KESEJAHTERAAN SOSIAL ANAK MENABUR CINTA KASIH KECAMATAN HAMPARAN PERAK - Dioranta, Sondang; Anifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sondang Dioranta Pane. 2026. The Process of Religious Character Formation of Foster Children at the Child Social Welfare Institution Menabur Cinta Kasih, Hamparan Perak District. Undergraduate Thesis, Community Education Study Program, Faculty of Education, Universitas Negeri Medan. This study was motivated by the condition of foster children at LKSA Menabur Cinta Kasih, most of whom come from vulnerable social backgrounds and grow up without prior religious foundation, requiring character formation to begin from a starting point of zero religious grounding. This study aims to describe the process of religious character formation among foster children at LKSA Menabur Cinta Kasih and to identify the supporting and inhibiting factors in that process. This study employed a qualitative method with a descriptive case study design. Data were collected through interviews, observation, and documentation involving four informants, consisting of two institutional staff members (the chairperson and secretary) and two foster children, then analyzed through data reduction, data display, and conclusion drawing. The findings show that the process occurs systematically through three interrelated components based on Thomas Lickona's theory (1991)—knowing, desiring, and doing the good—supported by habituation and caregivers' role modeling (Putriani and Pasaribu, 2024), and developing from a natural stage toward an awareness stage (Gawoh, 2020, as cited in Atfal et al., 2023). Supporting factors include a religious and conducive institutional environment, the active role of caregivers as role models, and structured religious programs, while inhibiting factors include the children's diverse backgrounds, low religious awareness in the early stage, carried-over negative habits, and emotional conditions, addressed through a humanistic personal approach. The study concludes that religious character formation runs holistically, with consistency in guidance as the key to its success.